International Student Exchange in Australian Social Work Education. Issue 4 (2nd October 2017) - Harris, Nonie; Miles, Debra; Howard, Elise; Zuchowski, Ines; King, Julie; Dhephasadin Na Ayudhaya, Piyachat; Jones, Peter; Francis, Abraham; Gopalkrishnan, Narayan; Puthantharayil, George
ABSTRACT: International student exchange is pursued by Australian schools of social work as a strategy to engage with the internationalisation agenda set by government, universities, and the profession. However, little concrete information about the nature and scope of these activities exists. The study reported here aimed to address this gap. Twenty-seven of the 30 Australian universities that offer social work programs participated in an online survey about international student exchange activities. The results indicate that a majority of schools ( n = 23) do engage in such activities, with international field placements the most frequent form of exchange. Exchanges are most likely to be facilitated and managed by social work staff. The findings, and their implications for the development of good practice in international student exchange, are discussed. This research provides a "point-in-time" snapshot of international exchange in Australian social work education and a benchmark for future analyses of this expanding practice in the profession.